2015
DOI: 10.1186/s12936-015-0672-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of K13-propeller polymorphisms in Plasmodium falciparum from China-Myanmar border in 2007–2012

Abstract: BackgroundThe recent emergence and spread of artemisinin resistance in the Greater Mekong Subregion poses a great threat to malaria control and elimination. A K13-propeller gene (K13), PF3D7_1343700, has been associated lately with artemisinin resistance both in vitro and in vivo. This study aimed to investigate the K13 polymorphisms in Plasmodium falciparum parasites from the China-Myanmar border area where artemisinin use has the longest history.MethodsA total of 180 archived P. falciparum isolates containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 30 publications
(42 reference statements)
11
96
0
Order By: Relevance
“…Besides, our recent analysis of the K13 gene in longitudinally collected samples from this study area showed increasing prevalence of parasites carrying mutations in the kelch domain, suggesting artemisinin resistance may also be evolving in this area. 34 Furthermore, given the recently documented failure of DP in Cambodia, continuous monitoring of clinical efficacy of ACT is warranted to deter the emergence and contain the potential spread of artemisinin resistance. …”
Section: Discussionmentioning
confidence: 99%
“…Besides, our recent analysis of the K13 gene in longitudinally collected samples from this study area showed increasing prevalence of parasites carrying mutations in the kelch domain, suggesting artemisinin resistance may also be evolving in this area. 34 Furthermore, given the recently documented failure of DP in Cambodia, continuous monitoring of clinical efficacy of ACT is warranted to deter the emergence and contain the potential spread of artemisinin resistance. …”
Section: Discussionmentioning
confidence: 99%
“…A mutation in codon 554 has also been found in one isolate each from Kenya (15), Mali (16), and Senegal (unpublished data). The F495L mutation has been found in two isolates from the China-Myanmar border (17).…”
mentioning
confidence: 99%
“…Amino acid mutations, i.e., A676D and H719N (near 675 and 720 codons, respectively), of K13 propeller blade VI have been described recently from China-Myanmar border in low frequencies. 16 Despite the actual role, we assume that D702N mutation might have emerged independently in this region and further evidence in future will unlock an approach for validation of its role in artemisinin resistance. However, A675V allele has been observed in frequency next to A481V allele.…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, it has been explained that C580Y, F446I, and P574L mutations along with other mutations in kelch propeller domain associated with artemisinin resistance are collectively spreading in a rapid manner towards upper Myanmar and extending up to regions near India. 16 Also, F446I mutation has been considered as the most prevalent in China-Myanmar border than other mutations. 24 Recently, G533A novel mutation has been reported in P. falciparum isolates of Northeast region, India along with other non-synonymous S549Y,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation